Peran Pendamping Sosial Dalam Memotivasi KPM PKH Desa Dukuhkarya Melalui Pendidikan Islam - Ricky Nugraha Sartono; Undang Ruslan Wahyudin (At Turots: Jurnal Pendidikan Islam, 2022)
Social Assistants carry out their role in motivating KPM PKH through Family Capacity Building Meetings (P2K2) activities. Social Facilitators believe that PKH KPM can convince themselves to live independently without the help of other people or the government, so that PKH KPM can escape poverty. Social Facilitators provide motivation through P2K2 activities which are expected to improve abilities and change mindsets. The role of Social Facilitators is needed by KPM PKH to build awareness that they can live independently and escape poverty. The research method used in compiling this writing is qualitative research by analyzing data accompanied by relevant references so that it is easy to understand how the role of Social Facilitators plays a role in motivating KPM PKH to get out of social problems. Social Facilitators through P2K2 convey, convince KPM PKH how to become better parents and become independent families, so they can escape poverty